Reconstructing Digital Learning Ethics in Islamic Religious Education Through the Integration of Maqāṣid Al-Sharīʿah and Huma Betang Values - Nur Wakhidah; Yaya Riana; Sri Hidayati; Zakaria Ahmad (JURNAL AT-TURAS, 2026)
The rapid expansion of digital technologies has transformed Islamic Religious Education by generating ethical challenges such as cyberbullying, misinformation, online hostility, declining empathy, and irresponsible digital behavior. While previous studies have examined Maqāṣid al-Sharīʿah, local wisdom traditions, and digital ethics separately, their integration as a framework for digital learning ethics remains underexplored. This study aims to reconstruct digital learning ethics in Islamic Religious Education through the integration of Maqāṣid al-Sharīʿah and Huma Betang values. Employing a qualitative library research design, the study utilized thematic content analysis, comparative analysis, and hermeneutical interpretation. The corpus comprised 63 scholarly sources, including classical Islamic legal and maqāṣid texts, contemporary studies on Islamic ethics, research on Huma Betang philosophy, and empirical studies on digital ethics and Islamic education. The findings indicate that contemporary digital challenges cannot be adequately addressed through legal compliance alone. Although Maqāṣid al-Sharīʿah and Huma Betang differ in their epistemological foundations, they converge in promoting justice, human dignity, compassion, collective welfare, cooperation, and social responsibility. The study proposes Cultural Maqāṣidization as a conceptual framework explaining how Islamic ethical objectives are translated into culturally grounded educational practices through local wisdom. This framework contributes to Islamic ethics, maqāṣid studies, and Islamic Religious Education by advancing a culturally mediated model of digital learning ethics that is both normatively grounded and contextually relevant.